2015
DOI: 10.3906/sag-1407-67
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of hair and serum trace elements in patients with Alzheimer disease and healthy participants

Abstract: Background/aim: To determine whether there was a difference between serum and hair trace elements' concentrations in patients with Alzheimer disease (AD) and healthy participants. Materials and methods:Hair and serum copper, selenium, zinc, magnesium, manganese, and iron levels were measured by inductively coupled plasma-mass spectrometry in patients with AD and healthy participants, and the obtained results were statistically compared. Results:The mean hair selenium and zinc levels of patients with AD were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 36 publications
(37 reference statements)
0
31
1
Order By: Relevance
“…Of the remaining 66, 51 irrelevant studies were excluded by reviewing the title and abstracts. A total of 15 full text articles [7][8][9][10][11][12][13][14][15][16][17][18][20][21][22] were thoroughly reviewed for their inclusion. Of these, 3 duplicate articles were excluded [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the remaining 66, 51 irrelevant studies were excluded by reviewing the title and abstracts. A total of 15 full text articles [7][8][9][10][11][12][13][14][15][16][17][18][20][21][22] were thoroughly reviewed for their inclusion. Of these, 3 duplicate articles were excluded [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…As an antioxidant it protects OS mediated cell damage through a series of selenoproteins mainly glutathione peroxidase (GPx) and selenoprotein P [2,6]. The results of the available studies on selenium levels in AD are inconsistent [7][8][9][10][11][12][13][14][15][16][17][18]. While some studies have shown that AD patients have lower selenium levels [7,9,10,14,16,17], others [8,[11][12][13]15,18] have contrariwise reported an increased or no change.…”
Section: Introductionmentioning
confidence: 91%
“…Excess zinc favors formation of zinc-Ab (b-amyloid) complexes, b-amyloid precursor protein expression, and plaque burden (10,11,17). Furthermore, zinc deposition in amyloid in the brain appears to deplete zinc from other body systems, resulting in low hair and serum levels (10,11,16,17,(20)(21)(22)(23). Studies have also shown that copper and manganese levels in hair are higher and selenium level is lower in patients with Alzheimer's disease than in healthy controls (21,22), and magnesium levels in cerebrospinal fluid in patients with Alzheimer's disease is lower than in healthy controls (22).…”
Section: Series Of Reviews On Carbohydrates Wheat and Cereal Grainsmentioning
confidence: 99%
“…Furthermore, zinc deposition in amyloid in the brain appears to deplete zinc from other body systems, resulting in low hair and serum levels (10,11,16,17,(20)(21)(22)(23). Studies have also shown that copper and manganese levels in hair are higher and selenium level is lower in patients with Alzheimer's disease than in healthy controls (21,22), and magnesium levels in cerebrospinal fluid in patients with Alzheimer's disease is lower than in healthy controls (22). Redox-active minerals such as copper and iron can promote oxidation, which is thought to occur early in the process of neurodegeneration and is a hallmark of both Alzheimer's disease and Parkinson's disease (15)(16)(17)24,25).…”
Section: Series Of Reviews On Carbohydrates Wheat and Cereal Grainsmentioning
confidence: 99%
“…[4] [5] [6]. In order to improve the concentration of selenium in the maifanite concentrate, we designed the orthogonal experiments from six factors: size of maifanite, concentration of maifanite, soaking time at room temperature, heating temperature, heating time and pH value.…”
mentioning
confidence: 99%